KELAS IBU HAMIL MEMPUNYAI PENGARUH POSITIF TERHADAP TINGKAT KECEMASAN IBU PRIMIGRAVIDA MENGHADAPI PERSALINAN - Theresia Eugenie Eugenie; Delmaifanis Delmaifanis Delmaifanis; Meriam Napitupulu Napitupulu (Poltekkes Kemenkes Jakarta III, 2014)
Anxiety is an emotional disturbance that is often felt by pregnant women, especially in primigravida. One of the government programs in improving maternal health is to hold classes for pregnant women. The purpose of this study was to determine the effect of maternal class to decreased levels of maternal anxiety facing childbirth. Research methods: a quasiexperimental study with a pretest and posttest design with a control group. Subjects were primigravida pregnant mothers who attend classes 30 people and mothers who do not attend classes as much control as 30 people. Sampling technique with quota sampling. Data collection tools used anxiety scale HARS. Data analysis was done with independent t-test, using 5%. Results of the study: there are differences in the mean levels of anxiety in primigravida mother after classes. The results show the mean pretest in the experimental group control group 40.33 41.97. The results of the treatment group posttest mean 31.63, 42.87 control group. The results of the t test p-value 0.00 posttest. means at 5% -class mothers no relationship with the level of anxiety to face delivery. Conclusion: There is a class effect of the decrease in the level of maternal anxiety facing labor primigravida. Literatur: 20 (1992-2013)